Review on Wetland Ecosystem Destruction - Amenu, Bekele Tona; Mamo, Getahun Shanko (International Journal of Scientific Research in Civil Engineering, 2017)
Ecosystem services lie at the heart of interactions between society and nature. Wetlands are natural assets that can deliver ecosystem services from local to regional scales. Due to their unique characteristics, they influence global biogeochemical and hydrological cycles in spite of their scattered nature. The idea of the ‘‘wise use of wetlands’’ derives from intergovernmental treaty the Convention on Wetlands held in Ramsar, Iran, in 1971. Wetlands continue to decline globally, both in area and in quality. Depending on the region, 30–90 % of the world’s wetlands have already been destroyed or strongly modified in many countries. Because of wetland losses and degradation, people are deprived of the ecosystem services that wetlands provide. Wetland resources in Ethiopia are not fully documented. In Ethiopia, wetland management is not efficiently coordinated and lacks adequate policy support. The attitudes of people about wetlands have shifted enormously over the past several decades. When both the marketed and non-marketed economic benefits of wetlands are included, the total economic value of unconverted wetlands is often greater than that of converted wetlands. Traditional and modern agricultural expansions, continuous land degradations, urbanizations and industrializations, lack of policies and institutional arrangements, lack of capacities, natural and ecological problems are the most dominant challenging factors of wetlands. Conservation of wetlands is a relatively recent priority, and it has seen more recent shifts from protection of remaining wetlands initially as a static biodiversity resource towards a focus on the many, formerly largely undervalued beneficial functions that these ecosystems provide to society.
Keywords: Wetland; Wetland Ecosystems; Conservation; Destruction